Assessment of Knowledge of Parents of Children with Cortical Visual Impairment: An Interventional Study - Lama, Ang Jangmu; Adhikari, Srijana; Parajuli, Rojeeta (Nepalese Journal of Ophthalmology, 2023)
Introduction: The cornerstone of CVI management is developing methods to help the kid, caregiver  and educator comprehend how the child uses their vision and how modifications may be made to help the child use it more effectively.Objectives: To evaluate caregivers' and parents' understanding of cortical visual impairment and how it evolves after receiving educational materials in the form of video and handout.Materials and methods: This prospective interventional study enrolled all children with CVI at a tertiary eye care center from 2020 February to 2021 January. Parents were interviewed about CVI visual behaviour using a Perkins website consulting interview. They were then sensitised with a Nepali video and handout describing CVI characteristics. A follow-up visit or call was scheduled six weeks later to reassess their knowledge.Results: In the study, 37 parents participated. Before the intervention, 81.1% (n = 30) were unaware of CVI, which decreased significantly to 4.3% (n = 1) after intervention (p